Abstract state machines, Alloy, B, TLA, VDM, and Z : 6th International Conference, ABZ 2018, Southampton, UK, June 5-8, 2018, Proceedings /: 6th International Conference, ABZ 2018, Southampton, UK, June 5-8, 2018, Proceedings. (2018) - Unknown
No abstract available